ESTRUS INDUCTION, FERTILITY AND BIOCHEMICAL PROFILE IN TRUE ANESTRUS SURTI BUFFALO FOLLOWING DIFFERENT ESTRUS SYNCHRONIZATION PROTOCOLS - PATEL, AJ; PATEL, JA; DHAMI, AJ; PRAJAPATI, JP; PARMAR, SC (The Indian Journal of Animal Reproduction, 2022)
Under field conditions, postpartum (>90d) true anestrus Surti buffalo treated with four different hormonal protocols (n=11 each), viz., Doublesynch, Estradoublesynch, Triu-B/PRID, PRID+PMSG and untreated control revealed 81.8-100% estrus induction response. The respective conception rates obtained following AI at induced estrus was 27.3, 27.3, 18.2 and 45.4%, with an overall conception rate of three cycles as 63.6, 54.5, 63.6 and 81.8%, which was much higher than control buffalo (18.2%). Plasma cholesterol between conceived and nonconceived buffalo was different (p<0.05) on day 12 post-AI in Doublesynch and on day of PG injection in PRID protocol. In brief, all four protocols can be used successfully to induce estrus and improve fertility in postpartum anestrus buffalo without altering the plasma protein or cholesterol profile.